FASE-FASE PERKEMBANGAN: FASE-FASE PERKEMBANGAN - rahmatia inaku; Rahmat Olii; Urik Taurik (LPPM UNiversitas Bina Mandiri Gorontalo, 2021)
Developmental phases refer to a series of stages experienced by individuals in the process of growth and development throughout their lives. This concept has been a topic of constant research by psychologists and human development. This article discusses the phases of human development which include the prenatal, infant and toddler phases, childhood, adolescence, early adulthood, middle adulthood, and late adulthood. Each phase has specific characteristics that affect the physical, social, emotional and cognitive development of the individual.